Samorząd terytorialny w strukturze aparatu państwa (perspektywy przebudowy administracji lokalnej) - Rabska, Teresa (Wydział Prawa i Administracji UAM, 1993)
The reconstruction of public administration is one of the most important structural tasks. Decentralization through Self- government is the most advanced form of the enforcement of public administration. However, it is not a sufficient reorganization undertaking. For decentralization to be efficiently implemented, certain general conditions should be met. One of them is a deep reconstruction of t he central government administration, which in its present form is not correlated with a new political structure of the State, its new tasks and with a new position of Government (as set forth in the Constitutional Act of 17 October 1992). Besides, there exists a need to provide for a smooth course of, and correlation between, the making of politics by the Government and the functioning of the administrative apparatus. In such a context, a new conception of creating districts (powiaty) as a new unit of territorial division and self-governmental authority seems premature. It needs to be added that the position of a district in the draft Law is not unequivocal. In particular, it is not clear to what extent the district bodies are to represent the district community, and to what extent they will only be the executors of certain tasks set forth in the Law.
Local self-government in the structure of the state (prospects of the reconstruction of local administration)